2015
DOI: 10.5114/jcb.2015.55293
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of source-positioning uncertainty in high-dose-rate balloon brachytherapy of breast cancer

Abstract: PurposeTo evaluate the dosimetric impact of source-positioning uncertainty in high-dose-rate (HDR) balloon brachytherapy of breast cancer.Material and methodsFor 49 HDR balloon patients, each dwell position of catheter(s) was manually shifted distally (+) and proximally (–) with a magnitude from 1 to 4 mm. Total 392 plans were retrospectively generated and compared to corresponding clinical plans using 7 dosimetric parameters: dose (D95) to 95% of planning target volume for evaluation (PTV_EVAL), and volume co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These results may not be directly transferable to our technique due to differences in the type of catheter used. Kim [ 9 ] studied the source-position uncertainty in HDR balloon brachytherapy for breast cancer and concluded that for the balloon applicator, a ± 0.2 cm tolerance for source position accuracy was acceptable in most clinical cases. Again, these results cannot be directly compared to our technique due to differences in applicator and target volume definition.…”
Section: Discussionmentioning
confidence: 99%
“…These results may not be directly transferable to our technique due to differences in the type of catheter used. Kim [ 9 ] studied the source-position uncertainty in HDR balloon brachytherapy for breast cancer and concluded that for the balloon applicator, a ± 0.2 cm tolerance for source position accuracy was acceptable in most clinical cases. Again, these results cannot be directly compared to our technique due to differences in applicator and target volume definition.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of this effort is to demonstrate feasibility of a novel combination thermobrachytherapy balloon device that should facilitate new clinical trials to investigate simultaneous heat and radiation delivered uniformly and welllocalized in tumor bed immediately after surgery, before tumor cell migration into surrounding normal brain. This initial study focuses on thermal performance of a TBT balloon since the dosimetry of HDR radiation from within an implanted balloon catheter source is already well-characterized in the literature for soft tissue sites including brain and breast [9,29,30]. Subsequent in vivo studies and clinical trials with the proposed thermobrachytherapy device will be required to determine: (a) optimum balloon temperature and penetration depth of therapy for brain; (b) optimum brachytherapy dose for combined therapy; (c) optimum fractionation of heat and brachytherapy; and (d) whether combination strategies of thermobrachytherapy with EBRT, chemotherapy, temozolomide, and/or immunotherapy would be beneficial for GBM and other resected brain tumors.…”
Section: Introductionmentioning
confidence: 99%